Quantum Fisher information for unitary parametrization processes governed by arbitrary Lie algebras. (9th July 2018) - Liang, Hongbin; Yao, Fei; Jing, Xiao-Xing; Zhou, Yujue; Wang, Xiaoguang
Abstract: Quantum Fisher information (QFI) is a key concept of quantum metrology, which is widely used in quantum parameter estimation. We introduce a general approach to analytically get the QFI of pure states for unitary parametrization processes governed by arbitrary finite dimensional Lie algebras. We show the universality of this approach by comparing the result of algebra with the previous work and applying it to and algebras. For case, there are some interesting findings. The phase of the initial coherent state has an optimal value for maximum QFI, and the QFI can vanish and revive during the time evolution.